Ten to 15-Year Outcomes of Monoblock Uncemented Dual Mobility Cups - Cécile Batailler, MD, PhD; Sébastien Lustig, MD, PhD; Emmanuel Balot, MD, PhD; Frédéric Farizon, MD, PhD; Michel Henri Fessy, MD, PhD; Rémi Philippot, MD, PhD (JBJS Open Access)
Background:. Dual mobility cups (DMCs) have effectively prevented dislocations after total hip arthroplasty (THA). However, use of these cups in primary THAs remains controversial, especially in young patients. This study aimed to determine the long-term survival rate and functional outcomes of a contemporary DMC used in primary THA. Methods:. This retrospective multicenter study identified a cohort of 614 primary THAs performed with the same uncemented monoblock DMC between 2007 and 2010. Survival analysis included 572 THAs, while clinical analysis involved 394 THAs at a minimal follow-up of 10 years. The mean follow-up was 11.1 ± 1.2 years. The mean age was 71.4 ± 11.7 years, with 4.2% of patients under 50 years old. The mean body mass index was 27.0 ± 5.3 kg/m2. The 10-year Kaplan-Meier survival rate was calculated based on cup removal for any reason or cup revision for an aseptic reason as the end point. Harris hip scores were collected at the last follow-up. Results:. The cup-revision-free survival rate was 98.6% at 10 years and 96.2% at 13 years. No cup revisions were reported due to aseptic loosening or dislocation. The cup revisions were due to infection (7 of 572; 1.2%), acetabular fracture (1 of 572; 0.17%), and psoas impingement due to cup malpositioning (n = 1 of 572; 0.17%). Only 3 dislocations (0.52%) were observed, and they did not require revision. The mean Harris hip score significantly improved from 54.1 ± 14.4 preoperatively to 88.0 ± 14.3 at the last follow-up (p < 0.0001). For patients under 50 years old at the time of surgery, the mean Harris hip score showed significant improvement from 53.0 ± 10.2 preoperatively to 89.7 ± 12.8 at the last follow-up (p < 0.0001), with no significant difference compared with the older patients (p = 0.50). No revision or complication was reported in the younger patient population at 13 years of follow-up. Conclusions:. The monoblock uncemented DMC demonstrated excellent survival rates with no DMC-specific complications during a minimum 10-year follow-up. The dislocation rate was very low, and a younger age was not identified as a risk factor for failure. Therefore, monoblock cementless DMCs can be safely used, even in primary THA. Level of Evidence:. Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.